Sleeping Late at Night: Does it Affect the Performance of Futsal Athletes? - Wahyudi Widada; Ahmad Sulaiman (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Adequate sleep is crucial for optimal physiological and physical performance in athletes. This study aims to examine the effects of late-night sleep on cardiovascular responses and fitness levels among futsal athletes at the Muhammadiyah University of Jember. Using a pre-experimental design, ten athletes from the university’s futsal unit were purposively selected as participants. Measurements of systolic and diastolic blood pressure, heart rate, and cardiorespiratory endurance (VO₂Max) were conducted before and after a three-day period of restricted sleep. Data were analyzed using the Wilcoxon and paired t-tests. The findings revealed significant increases in systolic and diastolic blood pressure as well as heart rate after the sleep deprivation period, accompanied by a significant decrease in VO₂Max scores (p = 0.021). These results indicate that late-night sleep negatively affects athletes’ fitness by elevating cardiovascular strain and reducing aerobic capacity. The study emphasizes the importance of maintaining proper sleep hygiene as an essential recovery component in athletic training programs to sustain endurance, optimize performance, and prevent fatigue-related declines.